CHARACTERISTICS OF PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Diah Kharisma (Jurnal Medika Hutama, 2021)
Parents' social support is needed when having a child with Autism Spectrum Disorder (ASD) to control and prevent severity. The characteristics of parents who have ASD children are very important to identify in order to prevent stress. This study was aimed to identify the characteristics of parents with ASD children, namely age, education, gender, occupation, and social support. The results showed that parents with ASD children had the characteristics of age <40 years, higher education, female gender, and work. Social support is also strong from the four aspects, namely emotional, instrumental, informational, and reward support.